2022
DOI: 10.21608/ejchem.2022.109501.5016
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of antioxidant and anti-inflammatory activities of Parmotrema hypotropa lichen extract

Abstract: Lichens are used since antiquity for multiple therapeutic purposes, treating infections, fever, convulsions, and wounds. This study was designed to evaluate the antioxidant and anti Hale. The total phenolics and flavonoids content were determined in ethanol extract; the antioxidant activity was assessed by different chemical assays DPPH (1,1acid)), β-carotene-linoleic acid, reducing power, and further tested in vitro, for its anti-inflammatory effect through the bovine serum albumin denaturation assay; inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(52 reference statements)
0
0
0
Order By: Relevance
“…Absorbance values of these extracts and standard antioxidants were assessed at 24.75 µg/mL [9,12]. Further, Tartouga et al, the extract demonstrated a 38.39% inhibition of BSA denaturation at a concentration of 1000 µg/mL [23]. Tatipamula et al reported that extracts from lichen had significant anti-inflammatory properties in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Absorbance values of these extracts and standard antioxidants were assessed at 24.75 µg/mL [9,12]. Further, Tartouga et al, the extract demonstrated a 38.39% inhibition of BSA denaturation at a concentration of 1000 µg/mL [23]. Tatipamula et al reported that extracts from lichen had significant anti-inflammatory properties in vitro.…”
Section: Discussionmentioning
confidence: 99%